RELAŢIA DINTRE STILUL DE ATAŞAMENT ŞI ATITUDINEA FAŢĂ DE DEBUTUL VIEŢII SEXUALE LA ADOLESCENŢII DE 16-18 ANI - USM ADMIN (Moldova State University, 2009)
The current research focuses on the detrimental effects of attachment styles and parental discusses on sexual issues with teenagers on adolescents sexual attitudes and birth control responsibility. Findings indicate that insecure attachment styles are correlated with higher permissiveness and instrumentality than secure attachment, excepting disorganized style- having the lower level of permissiveness and instrumentality. In addition, boys tend to have a higher level of birth control responsibility than girls, gender difference being insignificant. Regarding attitudes about the premarital sexuality, girls were less permissive, preferring a serious relationship before the outset of sexual activity in adolescence, unlike boys which considered the first months of a relationship an admissible background for the dawn of sexual relationship.